Legal Protection of Customer Personal Data in the Banking Sector - Wulan Rannie B. (ARRUS Journal of Social Sciences and Humanities, 2023)
In banking, what becomes a bank secret is all forms of personal data about customers and their deposits. With the current technological advances, banks are expected to be able to provide faster, easier, and safer services in transactions process. However, it is undeniable that during the transactions process, a risk for both banks and customers of data theft is done by other parties. This research is legal research using normative juridical legal research or library legal research carried out by examining library materials or secondary research sources consisting of primary legal materials, secondary legal materials, and tertiary legal materials. Based on the research results, there are several rules that can protect personal data, that are Law No. 10 of 1998 concerning Amendments to Law No. 7 of 1992 concerning Banking, Financial Services Authority Regulation (POJK) No. 11/POJK.03/2022 dated 6 July 2022 concerning the Implementation of Information Technology by Commercial Banks, and Law No. 27 of 2022 dated 17 October 2022 concerning the Protection of Personal Data. Based on these regulations, it is clear that they cannot fully protect banks and customers from personal data leaks. In addition, there are no regulations with concrete steps to protect personal data so that banks can implement risk management in data protection.